Faktor Fundamental Internal dan Eksternal Common Stock Market Prices Sektor Konstruksi dan Properti Periode 2013 – 2017 - Erric Wijaya; Tiqisha Putri Fadillah; Kania Nastiti Krisnandya; Fahreza Putranda; Sarah Hani Mahdiyah (STIE Indonesia Banking School, 2018)
This study examines the effect of Earnings per Share (EPS), Dividend per Share (DPS), and Book Value per Share (BVPS) and the influence of Gross Domestic Products (GDP) on stock market prices in Indone-sia Stock Exchange (IDX). All construction and property sector companies are consistently listed on the BEI and publish annual reports during the observation period (2013-2017) included in this study. In addi-tion, all data used for analysis is available ie EPS, DPS, BVPS. As a result, there are only 10 companies listed on the Indonesia Stock Exchange (IDX). Four hypotheses are under consideration in this study. Mul-tiple regression methods were used in this study, the correlation method used to support the findings. This study found significant influence of EPS, DPS, GDP on stock market price in Indonesian Stock Exchange (IDX).